Designing and governing country platforms: What role for the MDBs? - Archie Gilmour; Josué Tanaka; Sarah Colenbrander (ODI, 2024)
Country platforms are increasingly considered a practical solution to the many coordination and financing challenges that have long beset national development agendas, yet there is still debate over their definition, scope and implementation. This paper seeks to bring clarity to that debate by drawing on guidance from the members of the G20 International Financial Architecture Working Group, staff across the MDBs, and policy-makers and practitioners at the heart of existing country platforms. Offering a new comparative analysis of the governance arrangements of established country platforms and the role of MDBs within them, the paper sets out recommendations for national governments and MDBs to advance the country platform agenda.
Keywords: 330; Climate finance; Energy; Environment; Climate change